Fatores determinantes para a decisão de servidores públicos na adesão à previdência complementar - Oliveira, Jorge Leonardo Mosquera Torres de (2016)
This study aims to identify the determining reasons that lead the public servant to join the pension funds. The limits of the organizational behavior theory and trust, predominant theoretical framework in this study are analyzed to: map the profile of the public servant enrolled in pension funds, to understand how trust influences the decision to join the pension plan and; to understand the reasons that restrain the adhesion. Alternatively we assess the main incentive policies for join the pension plan could be adopted by the pension funds. We have done ten semi-structured interviews with pension experts. The study results of this research show that a group of servants have a high propensity to join the pension plan and the lack of trust and information are the two main reasons for no adherence. To increase membership there is no single solution, but a combination of factors that can face those problems such as institutional governance mechanisms that give the public servant, some assurance as well as certification of institution and managers. The research also show that a main point to increase the membership to the pension is to change the way of joining the pension funds, from the express to presumed or automatic, contributing thereby, for standard maintenance of life in the advanced age of public servants.